Use of diffuse reflections in tunable diode laser spectroscopy - Masiyano, Dackson (Cranfield University, 2009)
Tunable diode laser absorption spectroscopy (TDLAS) is an optical gas sensing technique in which the emission frequency of a laser diode is tuned over a gas absorption line of interest. A fraction of the radiation is absorbed by the sample gas and this can be determined from measurements of initial intensity and the intensity transmitted through the sample. The amount of light absorbed is related to the gas concentration. Additional modulation techniques combined with phase sensitive detection allow detection of very low gas concentrations (several parts per million). The advantages of using TDLAS for trace gas sensing include; fast response times, high sensitivity and high target gas selectivity. However, the sensitivity of many practical TDLAS systems is limited by the formation of unintentional Fabry-Perot interference fringes in the optical path between the source and detector. The spacing between the maxima of these fringes, in particular those generated in gas cells, can be in the same wavelength range as Doppler and pressure-broadened molecular line widths. This can lead to (1) interference fringe signals being mistaken for gas absorption lines leading to false concentration measurements or (2) distortion or complete obscuring of the shape and strength of the absorption line, such that the sensitivity of the instrument is ultimately limited by the fringes. The interference fringe signals are sensitive to thermal and mechanical instabilities and therefore can not be removed by simple subtraction techniques. Methods that have been proposed by previous workers to reduce the effects of interference fringes include careful alignment of optical components and/or mechanically jittering the offending components. In general the alignment of the optical components is critical. This often leads to complex and fragile designs with tight tolerances on optical component alignment, and can therefore be difficult and expensive to maintain in field instruments. This thesis presents an alternative approach based on the deliberate use of diffusely scattering surfaces in gas cells as a means of eliminating spurious signals due to Fabry-Perot etalons. However, their use introduced laser speckle that contributed an intensity uncertainty to gas detection measurements. A methodology for investigating the laser speckle related intensity uncertainty has been developed and confirmed. The intensity uncertainty has been quantified for the different gas cell geometries employing diffusely scattering surfaces including integrating spheres. Methods for reducing the speckle related intensity uncertainty were also investigated and are presented. It has been shown that under the right circumstances robust gas cell designs that do not suffer from Fabry-Perot etalon effects and are relatively easy to align can be realised. The performance was found to be comparable to a conventional cell design (e.g. 3ppm detection limit for a 10cm standard cell and 11ppm for a 10cm diffusive cell). The technique could potentially simplify instrument design, thereby aiding the transfer of technology to industry.